اقامتِ دین اور اس کا طریق ِکار :مولانا مودودی کے نقطۂ نظر کا مطالعہ: Iqāmat-e-Dīn and its Procedure: A Study of Mawdūdī’s Perspective - Hafiz Muhammad Imran; Dr. Ali Akbar Alazhari; Dr. Mehboob Ali Shah (Al-Qamar, 2019)
Iqāmat-e-Dīn or Establishment of religion has been a frequently discussed Idea in Islamic literature particularly in the Subcontinent. This paper studies Mawlānā Mawdūdī’s idea on the subject. It finds Mawdūdī’s concept quite different from other thinkers. Mawdūdī emphasizes the use of Islamic state and power for Islamic ideals, while some other thinkers, reject the centralization of the role of state and emphasize the importance of the individual. Both these ideologies seem to be somewhat exaggerated. The fact is that neither secular ideology nor the idea that the real purpose of religion is politics and government is correct. The work of promulgation of religion in all spheres of life will not be accomplished by force or coercion; it will be done by changing the minds of the people.